The Blessings of Medicine? Patient Characteristics and Health Outcomes in a Ugandan Mission Hospital, 1908–1970. (16th March 2019) - Doyle, Shane; Meier zu Selhausen, Felix; Weisdorf, Jacob
Summary: This article sheds new light on the impact and experience of western biomedicine in colonial Africa. We use patient registers from Western Uganda's earliest mission hospital to explore whether and how Christian conversion and mission education affected African health behaviour. A data set of 18, 600 admissions permits analysis of patients' age, sex, residence, religion, diagnoses, duration of hospitalisation and treatment outcomes. We document Toro Hospital's substantial geographic reach, trace evolving treatment practices and highlight significant variation in hospital-based disease incidence between the early colonial and early postcolonial periods. We observe no relationship between numeracy and health outcomes, nor religion-specific effects concerning hygiene-related infections. Christian conversion was associated with superior cure rates and shorter length of stay and with lower incidence of skin diseases and sexually transmitted infections (STIs). However, our findings indicate that STI incidence was linked to morality campaigns and that clinicians' diagnoses were influenced by assumptions around religious groups' sexual behaviour.